2017
DOI: 10.1002/jpln.201700249
|View full text |Cite
|
Sign up to set email alerts
|

Land use dynamics derived from colluvial deposits and bogs in the Black Forest, Germany

Abstract: The Black Forest is considered to be a rather unfavorable area, having a short vegetation period, low mean annual temperatures, high precipitation, and a pronounced relief. These conditions do not favor agricultural land use and thus it is widely accepted that people only began using the land intensively during the Middle Ages. In this integrated study 17 soil profiles, two peat bogs and a database of archaeological finds were used to reconstruct past land use impacts on the environment. AMS–14C datings of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…This paper focuses on the Swabian Jura and its land use history, which will be compared to the Black Forest [ 26 ] and the Baar area [ 19 ]. The regional focus of the study comprises favourable and unfavourable areas in low mountain ranges for practising agriculture due to the specific conditions of climate, topography and soils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper focuses on the Swabian Jura and its land use history, which will be compared to the Black Forest [ 26 ] and the Baar area [ 19 ]. The regional focus of the study comprises favourable and unfavourable areas in low mountain ranges for practising agriculture due to the specific conditions of climate, topography and soils.…”
Section: Introductionmentioning
confidence: 99%
“…The cuesta drops abruptly about 200–400 m in altitude into the Baar area, having rather favourable environmental conditions [ 19 ]. The southeastern Black Forest is characterized by a high relief intensity, high annual precipitation, low mean temperatures and acidic soils [ 26 ].
Figure 2.
…”
Section: Introductionmentioning
confidence: 99%
“…The fact that charcoal samples from the spring source area of the river Brigach date into the Late and Final Neolithic may be an indication that humans followed the larger rivers as they entered this landscape. This is also suggested by archaeological finds from the western Baar (Ahlrichs et al, 2016) and by the fragment of a Neolithic blade made of Cretaceous chert found in the colluvial deposits at the spring source of the river Breg (Henkner et al, 2018c).…”
Section: The Black Forestmentioning
confidence: 56%
“…Total C and N contents (mass %) were analysed using oxidative heat combustion at 1150 • C in a He atmosphere (element analyser "vario EL III", Elementar Analysensysteme GmbH, Germany, in CNS mode). Soil organic C content (SOC) was determined using SOC = C total − CaCO 3 × 0.1200428, and soil organic matter (SOM) was calculated using the factor 1.72 (Ad-hoc- AG Boden, 2005;Eberhardt et al, 2013;Henkner et al, 2018c).…”
Section: Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation